IMPLEMENTASI PROGRAM TRANSISI BAGI SISWA AUTIS DI SMP - INTAN PERMATA SARI, DEVY (Jurnal Pendidikan Khusus, 2016)
Abstract This research had purpose to expose the implementation of transition program to autism children implemented by SMPN 4 Sidoarjo with the principle of Direktorat PKLK Dikdas. Based on the introduction study on December 5th, 2015 there was indication that the transition program to autism students in the school involved into school extra-curricular program. This research used the descriptive method of qualitative approach and the technique of data collection used observation, interview, and documentation while the data analysis of descriptive qualitative used the phase of data reduction, data display, and verification / concluding. This research result indicated that in implementing transition program for autism students, integrating transition program was done by establishing structured extra-curricular and the program of self developing in the form of handicraft and clothing science i.e. twice in a week for 2 hours per week and when the students got leisure time while food science involved in sub-subject matter of vocational implemented once in a week suitable with the plan of learning implementation which was arranged by the teacher. To support the transition program, the school had tried to cooperate with industry and trade world (DUDI) i.e. shoes trade but it did not get any response yet from the DUDI. The evaluation of transition program for autism students was orally done by special education teacher (GPK) and the partners. The evaluation established by GPK was uncertain depending on the development of the autism students during the transition program given.   Keywords: Transition program,  inclusive school